Evaluation of Legal Violations in Organ Transplantations According to Turkish Penal Code Article 25/2 - Atılgan, Mehmet; Deveci, Cemyiğit; Toksoy, İrem Tuğçe (The Bulletin of Legal Medicine, 2023)
Objective: Illegal organ transplantations are attempted from time to time by issuing fake IDs or using someone else’s identity to receive transplantation as soon as possible by bypassing the organ waiting list. In recent years, it has been requested by the Court of Cassation that the people who were alleged to have purchased organs be evaluated in terms of Turkish Penal Code (TPC) 25/2. This study aims to discuss the method of approach to these cases. Methods: The forensic reports prepared by the Department of Forensic Medicine of Akdeniz University Hospital between 01.01.2019 and 31.12.2021 were examined, and the cases that were sent by judicial authorities to be evaluated in terms of TPC 25/2 were included in the study. Results: A total of nine cases were identified. It was understood that five of these cases used fake IDs, as well as, in six cases the illegal transplants were identified after the completion of the transplantations. Conclusion: TPC Article 25/2 states that, in case of necessity, the person does not have any criminal responsibility regarding the behaviors they do to protect against a serious and certain danger which was directed at a right to which they, or another, were entitled where there are no other means of protection. Although end-stage renal disease is an important public health problem, there are treatment alternatives for patients with end-stage renal disease. As a result, it was concluded that these cases did not have a medical emergency that prevented hemodialysis or peritoneal dialysis before transplantation.